2021
DOI: 10.3892/or.2021.7953
|View full text |Cite
|
Sign up to set email alerts
|

Combination of miR‑143 and miR‑506 reduces lung and pancreatic cancer cell growth through the downregulation of cyclin‑dependent kinases

Abstract: Lung cancer (LC) and pancreatic cancer (PC) are the first and fourth leading causes of cancer-related deaths in the US. Deregulated cell cycle progression is the cornerstone for rapid cell proliferation, tumor development, and progression. Here, we provide evidence that a novel combinatorial miR treatment inhibits cell cycle progression at two phase transitions, through their activity on the CDK4 and CDK1 genes. Following transfection with miR-143 and miR-506, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…The deregulation of cell-cycle-dependent proteins may thus contribute to therapeutic effects of miR506-3p in PDAC therapy as well. This is also supported by a recent study demonstrating miR-506 mediated downregulation of CDK1 and CDK4 [ 18 ]. Moreover, the induction of reactive oxygen species and autophagy, as well as of alterations in mitochondrial potential and structure, are additional steps towards cellular stress response and cell death.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The deregulation of cell-cycle-dependent proteins may thus contribute to therapeutic effects of miR506-3p in PDAC therapy as well. This is also supported by a recent study demonstrating miR-506 mediated downregulation of CDK1 and CDK4 [ 18 ]. Moreover, the induction of reactive oxygen species and autophagy, as well as of alterations in mitochondrial potential and structure, are additional steps towards cellular stress response and cell death.…”
Section: Discussionsupporting
confidence: 78%
“…In parallel, PIM-3, a member of the proto-oncogene PIM family, was found upregulated in pancreatic cancer tissue and negatively correlated with miR-506 levels [ 13 ]. Reduced miR-506 expression was associated with pancreatic progression, while upregulated exerted inhibitory effects [ 14 , 15 , 16 , 17 , 18 ]. In this context, STAT3 [ 17 ] and sphingosine kinase 1 (SPHK1 [ 14 ]) were identified as direct targets, and miR-506 levels were described to be affected by the oncogenic lncRNA NEAT1 [ 15 ] or by rosmarinic acid [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that CDKs regulate cell cycle progression at several irreversible transition points with formation of different cyclin/CDK/CKI (cyclin kinase inhibitor) complexes involved at different cell cycle stages [32,33]. p27 and p21 belong to the CKI family and bind to such cyclin/CDK complexes as cyclin D1/CDK6, cyclin E1/CDK2, and cyclin A2/CDK2, C-Myc and P53 also exhibit indispensable effects on the proliferation, transformation, cellular death and cell cycle progression of mammalian cells [34], and their dysregulation or mutation may convert them into pure oncogenes to promote development and progression of cancer [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…First discovered in 2005 by Bentwich and colleagues, miR-506 belongs to an X-chromosome-linked miR cluster which is well conserved within primate species [7]. Several studies have identified miR-506 as an anti-cancer biomolecule in various cancer types, due to its abrupt dysregulation in various cancer phenotypes [8,9]. Moreover, miR-506's role as an anti-oncogenic miR is demonstrated by it targeting numerous biological pathways, such as through diminished epithelial-mesenchymal transition (EMT) mediated by TGF-β [10], inhibition of E-cadherin expression [11], targeting the PI3K/AKT pathway [12], and p53 response element activation [13].…”
Section: Introductionmentioning
confidence: 99%